Molecular Markers Associated With Chemical Analysis: A Powerful Tool for Quality Control Assessment of Copalchi Medicinal Plant Complex - Cristians, Sol; Bye, Robert; Nieto-Sotelo, Jorge (Frontiers in Pharmacology, 2018)
The copalchi complex, Hintonia latiflora, H. standleyana and Exostema caribaeum, is widely used in Mexico for treating diabetes and gastrointestinal disorders. The first therapeutic use for H. latiflora bark was registered in the “Florentine Codex” in the 16th century. The latest pharmacological and phytochemical studies revealed that the infusion of the leaves have hypoglycemic, antihyperglycemic and gastroprotective activities. For these reasons the monograph of the main copalchi species, H. latiflora, was recently added to the Mexican Herbal Pharmacopoeia. Nevertheless, quality control parameters are focused to the bark but not to the leaves. Moreover, information about other Rubiaceae species is needed. The main goal of this study was to generate molecular and chemical markers for quality control of the copalchi complex raw material. In addition, the resolution of the taxonomical ambiguity between H. latiflora and H. standleyana, as well as the testing of the molecular and chemical markers in different geographical batches, were aims of this study. The molecular markers and chemical profiles of the leaf infusions were generated considering three different populations for H. latiflora and separate individuals of the three species (HL, n=10; HS, n=3; EC, n=4). The molecular markers matK, rbcL, trnH-psbA, rpl32-trnL and ITS2 were tested for their discriminating capabilities. Chemical profiles of the leaf infusions were obtained by means of HPLC analyses using chlorogenic acid and 4-phenylcoumarins as chemical markers. The concatenated sequence of the molecular markers trnH-psbA, rpl32-trnL and ITS2 clearly distinguished the three taxa, clarifying the taxonomical ambiguity of the Hintonia genus. Additionally, the chemical profiles allowed the unequivocal identification of each species supporting the molecular results; the geographical origin of the samples did not modify neither the chemical profiles nor the concatenated sequence of H. latiflora, suggesting that it is a robust identity test. The complementary use of molecular and chemical markers will assure the quality of plant material used in traditional medicine for therapeutic purposes, and should be valuable new information for the National Health authorities as a part of the Mexican Herbal Pharmacopoeia.